Enhanced depolluting capabilities of microbial bioelectrochemical systems by synthetic biology - Le Tao; Maoyong Song; Guibin Jiang (Synthetic and Systems Biotechnology, 2023)
Microbial bioelectrochemical system (BES) is a promising sustainable technology for the electrical energy recovery and the treatment of recalcitrant and toxic pollutants. In microbial BESs, the conversion of harmful pollutants into harmless products can be catalyzed by microorganisms at the anode (Type I BES), chemical catalysts at the cathode (Type II BES) or microorganisms at the cathode (Type III BES). The application of synthetic biology in microbial BES can improve its pollutant removing capability. Synthetic biology techniques can promote EET kinetics, which is helpful for microbial anodic electro-respiration, expediting pollutant removing not only at the anode but also at the cathode. They offer tools to promote biofilm development on the electrode, enabling more microorganisms residing on the electrode for subsequent catalytic reactions, and to overexpress the pollutant removing-related genes directly in microorganisms, contributing to the pollutant decomposition. In this work, based on the summarized aspects mentioned above, we describe the major synthetic biology strategies in designing and improving the pollutant removing capabilities of microbial BES. Lastly, we discuss challenges and perspectives for future studies in the area.